Root meristems in Medicago truncatula tissue culture arise from vascular-derived procambial-like cells in a process regulated by ethylene - Rose, Ray J (Journal of experimental botany, 2006)
Leaf explants of Medicago truncatula were used to investigate the origins of auxin-induced root formation. On the application of auxin there is some callus formation (not the massive amount that occurs in response to auxin plus cytokinin) and roots appear shortly after the first visible callus. Histological examination reveals morphologically distinctive sheets of callus cells that emanate from the veins of the leaf explants and, within this cell type, root primordia are produced as well as some vascular tissue cells. What is suggested is that the vein-derived cells (VDCs) are procambial-like and function as pluripotent stem cells with a propensity to form root meristems or vascular tissues in response to added auxin. The development of root primordia from these pluripotent cells was clearly up-regulated by the use of the sickle (skl) mutant, which is a mutant impaired in ethylene signal transduction while the wild type and the sunn mutant, defective in auxin polar transport, produced similar numbers of roots. The skl mutant in generating many more roots concomitantly formed fewer vascular tissues. The root meristems differentiate similarly to normal roots producing a central cylinder of vascular tissue, which connects with the leaf explant veins. The VDCs appear to be derived from the cells of or near the phloem. The leaf observations suggest that a pool of stem cells exist in vascular tissue that, in combination with auxin and perhaps other factors, drive a diversity of plant development outcomes that is species specific. The way auxin interacts with other hormones is a key factor in determining the stem cell fate. The histological data in this study also assist in the interpretation of the molecular analysis of auxin-induced root formation in cultured leaves of M. truncatula